Determinan Kemiskinan di Kabupaten Kepulauan Meranti - Indah Wulan Sari; Dahlan Tampubolon; Lapeti Sari (JIP ( Jurnal Industri dan Perkotaan ), 2023)
Study this aims to (1) analyze influence amount population , education  and income per capita by together to poverty in the district Island Meranti, (2) analyze the most dominant factor influence poverty in the district Island Meranti. Study this use multiple linear regression analysis model. The results showed that variable amount population, education and income per capita by together take effect significant to poverty in the district Island Meranti. By partial, test to coefficient regression show that variable amount population take effect negative and significant to poverty in the district Island Meranti, variable education take effect positive and significant to poverty in the district Island Meranti and variable income per capita take effect negative and significant to poverty in the district Island Meranti.